The Social Dimension of Regional Integration in ECOWAS - Robert, René (Social Science Research Network, 2004)
Regional economic integration arrangements have their own purpose, legal framework, institutional set-up, history, and trajectory, and this paper aims to study these factors in relation to the Economic Community of West African States (ECOWAS). When dealing with regional integration, it is important to consider governance, trade liberalization, and its social impact. The paper focuses on the West African Economic and Monetary Union (WAEMU) and the Organization for the Harmonization of Business Law in Africa (OHADA) to analyze labour law harmonization, poverty reduction strategies for development, gender empowerment, and democratic participation. Suggestions to strengthen socio-economic development include promoting social dialogue and how the International Labour Organization and other institutions' can help with better integration in Western Africa. Ultimately, identifying and understanding the unique economic integration arrangements of certain communities can help develop their paths towards a fairer globalization for all.
10.2139/ssrn.908485
Keywords: ECOWAS; Integration; Regional; Social dimension; WAEMU

The powers of the Labour Court to review arbitration awards of the Commission for Conciliation, Mediation and Arbitration : a comparative study - Bezuidenhout, Susan Antoinette (University of South Africa, 2004)
A critical and in-depth discussion of the powers of the labour court to review arbitration awards of the Commission for Conciliation, Mediation and Arbitration, the application of the author's findings relating to common-law, legislation and case law and a critical analysis thereof. Special reference is made to the provisions of sections 145 and 158(1)(g) of the Labour Relations Act 66 of 1995 including, in particular, the alternative application thereof in practice and scope for improvement in order to address potential prejudice to parties occasioned by the compulsory nature of (certain) dispute resolutions. This thesis incorporates a comparative study of the British and German labour law systems with reference to the relevant appeal and/or review procedures (as applied in their tribunals/courts), together with a discussion and application of certain other provisions relevant to South Africa labour law.
Keywords: British Labour system; CCMA; Compulsory arbitration; Dispute resolution; German Labour system; Labour Court; Review procedure

Theories of the company, employees and takeover regulation - Johnston, Andrew (European University Institute, 2004)
Keywords: Consolidation of corporations; European Union countries; Labor laws and legislation; Merger of corporations; Social policy

Corporate governance: a practical and effective response to the challenges raised - Fridman, Josef J. (McGill University, 2004)
This thesis seeks to address corporate governance from both a practical as well as an academic perspective. It searches for solutions to self-interest and agency costs, problems that it is posited are innate to the anthropomorphism of the corporation and to the separation of management and ownership of widely held, publicly traded, corporations. Practically, this dissertation is anchored in experience, garnered from empirical research, based on in depth and general surveys, as well as detailed interviews. It examines the workings of corporations, including their boards of directors, of gatekeepers, of checks and balances and of shareholders and the relative importance and rationale for the roles that they play. Based on the academic and empirical efforts it is posited that self-interest and the funneling syndrome, (a process whereby information required for decision making is constrained and managed by those in control), almost always predetermines the outcome of the corporate formal decision making process involving the board of directors. This facilitates abuse. When it occurs and there appears to be no accountability, confidence essential to the capital markets, quite understandably, suffers. A hypothesis is advanced to explain the complexity of a potential failure of corporate governance through a relatively simple formula. It draws conclusions as to what is required to help address the challenges raised by the breakdown in effective corporate governance and to help instill greater investor confidence. A self-assessment mechanism to help quantify how effectively a corporation is dealing with corporate governance, both on an absolute basis (comparing itself year over year) and on a relative basis (compared to one's peers) is proffered. This tool of more effective corporate governance, seeks to identify the causes for breakdowns in corporate governance and to assist a board of directors in dealing more proactively with this challenge.
https://escholarship.mcgill.ca/concern/theses/nz8060241
Keywords: Corporate governance